Galectina-3 controla a proliferação intracelular de Toxoplasma gondii em células trofoblásticas humanas (linhagem BeWo) - Ribeiro, Mayara (2020)
Toxoplasma gondii is na intracellular parasite that causes toxoplasmosis. Infection by the parasite may be asymptomatic, however, clinical manifestations may occur, especially in immunocompromised individuals and in fetuses due to congenital transmission. In pregnant women, the infection can cause miscarriages, prematurity and / or fetal abnormalities. At the maternal-fetal interface, several types of cells and molecules contribute to fetal development, regulation of the immune system and defense against microorganisms. Galectin-3 (Gal-3) is a β-galactoside residue-binding lectin expressed in cells of placental microenvironment, including trophoblastic cells. This lectin is involved in several biological processes, including growth regulation, cell differentiation and migration, apoptosis, modulation of immune cell activity, pathogen recognition and infection control by intracellular parasites, such as T. gondii. However, little is known about the role of Gal-3 in the placental microenvironment during T. gondii infection. Thus, this work aimed to investigate the effect of Gal-3 on T. gondii infection in BeWo trophoblastic cells. For this, Gal-3 expression was sileced in BeWo cells by interference RNA (RNAi) (BeWo Gal-3 KD; KD: knockdown) or not (non-silenced cells (BeWo Gal-3)); subsequently, (i) intracellular proliferation, adhesion and invasion of the parasite; (ii) production of cytokines and reactive oxygen species (ROS) were determined in BeWo Gal-3 and BeWo Gal-3 KD cells. The results obtained showed that Gal-3: (i) controls the intracellular proliferation of T. gondii; (ii) decreases the adhesion of T. gondii; (iii) decreases the invasion of T. gondii; (iv) increases the production of the cytokine IL-6 regardless T. gondii infection; (v) does not interfere on ROS production in BeWo cells. Thus, Gal-3 appears to have a pro-inflammatory role in BeWo cells, which may be related to the lower parasitism observed in cells that express Gal-3. This was the first study to show the influence of Gal-3 on T. gondii control in trophoblastic cells.